2022
DOI: 10.1111/bph.15697
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term molecular differences between resilient and susceptible mice after a single traumatic exposure

Abstract: Background and Purpose: Post-traumatic stress disorder (PTSD) is a heterogeneous disorder induced by trauma, resulting in severe long-term impairments of an individual's mental health. PTSD does not develop in every individual and, thus, some individuals are more resilient. However, the underlying molecular mechanisms are poorly understood. Here, we aimed to elucidate these processes. Experimental Approach: We used a single-trauma PTSD model in mice to induce long-term maladaptive behaviours and profiled the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
(101 reference statements)
1
7
0
Order By: Relevance
“…Moreover, using animal models of stress, it was described that stress can affect gut microbial composition ( Gareau et al, 2007 ; Bharwani et al, 2016 ; Burokas et al, 2017 ; Pascual Cuadrado et al, 2021 ; Figure 2 ). Clinical studies also found changes in microbial composition in patients with a diagnosis of depression or anxiety disorder ( Bastiaanssen et al, 2019 ).…”
Section: Microbiota-gut-brain Axis and Stress Responses-potential Rol...mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, using animal models of stress, it was described that stress can affect gut microbial composition ( Gareau et al, 2007 ; Bharwani et al, 2016 ; Burokas et al, 2017 ; Pascual Cuadrado et al, 2021 ; Figure 2 ). Clinical studies also found changes in microbial composition in patients with a diagnosis of depression or anxiety disorder ( Bastiaanssen et al, 2019 ).…”
Section: Microbiota-gut-brain Axis and Stress Responses-potential Rol...mentioning
confidence: 99%
“…Indeed, the idea that diet might influence emotional responses has been established many years ago. Some studies found that certain species of bacteria are more abundant in resilient mice in comparison to control or susceptible mice ( Marin et al, 2017 ; Yang et al, 2017 ; Bassett et al, 2019 ; Pascual Cuadrado et al, 2021 ). Recently, we have demonstrated differences in gut microbial composition associated with a resilience outcome to a single trauma in mice ( Pascual Cuadrado et al, 2021 ).…”
Section: Microbiota-gut-brain Axis and Stress Responses-potential Rol...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this Themed Issue, through a series of reviews and research articles focused on the aetiology of specific diseases, their symptomatology and new treatment strategies, how these disorders might be prevented is discussed. Cuadrado et al (2022) address molecular fingerprints of resilient and susceptible phenotypes after a single traumatic exposure in mice.…”
mentioning
confidence: 99%